The prognostic implications and tumor-promoting functions of CHSY3 in gastric cancer - Wang, Han; Zhang, Junchang; Wei, Zhuoqi; Chen, Songyao; Zheng, Jiabin; Li, Yong (Frontiers in Immunology, 2024)
Chondroitin sulfate synthase 3 (CHSY3) is an important enzyme that regulates glycosylation, but its role in tumors has not been determined. Here, we showed that high CHSY3 expression promotes proliferation in gastric cancer (GC) cells and is associated with poor prognosis in GC patients. We analyzed the immunohistochemistry data of 150 gastric cancer patients to determine the clinicopathological and survival significance of CHSY3. Immunofluorescence was used to detect the colocalization of CHSY3 with infiltrating immune cells. Additionally, we also found that CHSY3 was present mainly in the tumor stroma and was more abundant in tumor tissues than in matched adjacent tissues. High CHSY3 expression was associated with more advanced tumor stage, higher recurrence risk and worse survival. Immunohistochemistry and bioinformatic analysis revealed that CHSY3 expression was significantly positively correlated with tumor-associated macrophage (TAM) infiltration. Moreover, after knocking down CHSY3, the proliferation of cells was decreased, and the migration ability was reduced, as shown by scratch, monoclonal and transwell assays. In conclusion, this study revealed that CHSY3 has a tumor-promoting effect on GC, suggesting a novel therapeutic strategy against this disease.